2022
DOI: 10.1038/s41467-021-27764-w
|View full text |Cite
|
Sign up to set email alerts
|

CD4 and CD8 co-receptors modulate functional avidity of CD1b-restricted T cells

Abstract: T cells recognize mycobacterial glycolipid (mycolipid) antigens presented by CD1b molecules, but the role of CD4 and CD8 co-receptors in mycolipid recognition is unknown. Here we show CD1b-mycolipid tetramers reveal a hierarchy in which circulating T cells expressing CD4 or CD8 co-receptor stain with a higher tetramer mean fluorescence intensity than CD4-CD8- T cells. CD4+ primary T cells transduced with mycolipid-specific T cell receptors bind CD1b-mycolipid tetramer with a higher fluorescence intensity than … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…CD4+ and CD8+ T cells are key links to immunoregulation in organisms. 34 CD8+ T cells are immune effector cells and responsible for the removal of target cells through a direct killing effect. 35 CD4+ T cells mainly consist of T-helper (Th) cells Th1, Th2, and Th17, and regulatory T-cells (Treg), which could be induced by different commensal microbiota.…”
Section: Effects Of Scp On T Lymphocyte Subpopulations In the Spleens...mentioning
confidence: 99%
“…CD4+ and CD8+ T cells are key links to immunoregulation in organisms. 34 CD8+ T cells are immune effector cells and responsible for the removal of target cells through a direct killing effect. 35 CD4+ T cells mainly consist of T-helper (Th) cells Th1, Th2, and Th17, and regulatory T-cells (Treg), which could be induced by different commensal microbiota.…”
Section: Effects Of Scp On T Lymphocyte Subpopulations In the Spleens...mentioning
confidence: 99%
“…Our research demonstrates that T cell recognition of GMM relies on T cell receptors (TCRs) and exhibits remarkable specificity toward the native GMM structure produced by mycobacteria. This suggests that T cells possess the capability to intricately discern the hydrophilic cap of an antigen, potentially functioning as a classical TCR epitope by direct interaction with the TCR variable region [ 51 , 52 ]. In addition, GMM must be synthesized with glucose provided by mammals, which means that GMM production can be used as a good indicator of local invasion of mycobacteria, and its detection by the host immune system is helpful for effective monitoring of mycobacterial infection [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of special interest was a population of CD8+GMM+GranzB+ Tconv that was not part of the prespecified manual gating but was identified by the Phenograph cluster analysis. This cell subset, which has only recently been described, was found in people with active TB, in whom CD8+GMM+ T cells displayed upregulated cytotoxic transcription profiles[56]. The authors concluded that this cell subset may contribute to the clearance of Mtb -infected host cells.…”
Section: Discussionmentioning
confidence: 96%